Analysis of methods for high-speed forming the relief microimages on metallic substrates - Kryuchin, A.A.; Pankratova, A.V.; Kassko, I.A.; Nagorny, F.V.; Chirkov, D.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2007)
The use of methods of ion and electrochemical etching of metallic substrates
to obtain relief microstructures with micron and submicron sizes is considered. Presented
are the results of experimental researches of processes aimed at manufacturing metallic
carriers by using inorganic photoresists.